2017
DOI: 10.1016/j.jvs.2017.07.120
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term readmission rates after infrainguinal bypass in a safety net hospital are higher than expected

Abstract: Short- and long-term readmission rates in a safety net setting are high. The 30-day rates in this study are higher than historically reported. This data sets baseline rates for 90-day and 1-year readmission for future analyses. Although the majority of short-term readmissions are related to the index procedure, long-term readmission rates are more frequently related to systemic comorbidities. Targeted patient interventions aimed at preventing the most common reasons for readmission may improve readmission rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…11 The individual complications rates in our study were also similar to those reported in the NSQIP, including MALE (2.8% vs 3.2%) and MACE (1.0% vs 1.7%). These complication rates were also consistent across multiple other databases, including analyses of institutional databases 18,19 and the Vascular Quality Initiative. 20 It is encouraging that the major complication rate associated with elective LEB has been consistently <10%.…”
Section: Discussionsupporting
confidence: 65%
“…11 The individual complications rates in our study were also similar to those reported in the NSQIP, including MALE (2.8% vs 3.2%) and MACE (1.0% vs 1.7%). These complication rates were also consistent across multiple other databases, including analyses of institutional databases 18,19 and the Vascular Quality Initiative. 20 It is encouraging that the major complication rate associated with elective LEB has been consistently <10%.…”
Section: Discussionsupporting
confidence: 65%
“…Also, patients who died during follow-up were not included in the analysis as demonstrated in previous studies that analyzed readmission for resource utilization. 5,21 Outcome variables collected at 30, 90, and 180 days were survival, readmission reasons, and reinterventions. Readmission reasons after the index TEVAR were identified by the primary ICD-9-CM diagnosis code and categorized by similarity.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown varied readmission rates for vascular surgery patients. [16][17][18][19][20][23][24][25][26] Medicare reports an average 30-day readmission rate of 24%, while an overall NSQIP analysis evaluating 86 238 vascular surgery patients found a 30-day readmission rate of 10%. 23,25 Damrauer et al specifically examined 30-day readmissions after LEB and found a readmission rate of 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Lower extremity bypass (LEB) has previously been shown to be very resource intensive with longer than expected hospital stays and higher readmission rates within the surgical global period. 19,20 It is unclear how hypoalbuminemia affects these metrics in the long term such as readmission and mortality within the 90-day surgical global period.…”
Section: Introductionmentioning
confidence: 99%